Adenosine Deaminase Two and Immunoglobulin M Accurately Differentiate Adult Sneddon's Syndrome of Unknown Cause - Santo, GC (2019)
The association that exists between livedo reticularis (LR) and stroke is known as Sneddon's syndrome (SnS). The disorder is classified as primary SnS (PSnS), if the cause remains unknown and secondary SnS. The condition is rare and it occurs mainly sporadically. In 2014, 2 independent teams described a new genetic disorder with childhood-onset, which was called deficiency of adenosine deaminase 2 (DADA2), characterized by recurrent fevers and vascular pathologic features that included LR and stroke. All the patients carried recessively inherited mutations in cat eye syndrome chromosome region candidate 1 gene (CECR1), encoding the adenosine deaminase 2 (ADA2) protein. Genetic testing is the standard for the diagnosis of DADA2. However, the diagnostic accuracy of more affordable laboratorial analysis in CECR1-mutated individuals remains to be established. We aim to determine whether plasma ADA2 activity and serum immunoglobulin M (IgM) levels can distinguish (1) DADA2 from other adult patients within the SnS spectrum, and (2) healthy CECR1 heterozygous (HHZ) from healthy controls (HC).